LO81: The use of in situ simulation to improve emergency department staff comfort with the management of high acuity, low occurrence cases. (May 2020) - Bilic, M.; Hassall, K.; Hastings, M.; Fraser, C.; Rutledge, G.; Hanel, E.
Abstract : Introduction: In the emergency department (ED), high-acuity presentations encountered at low frequencies are associated with reduced staff comfort. Previous studies have shown that simulation can improve provider confidence with practical skills and management of presentations in various fields of medicine. The present study examined the effect of in situ simulation on interprofessional provider comfort with the identification and management of high-acuity low-frequency events in the ED. It further assessed the feasibility of implementing weekly simulation as an interprofessional education initiative in a high-volume ED. Methods: This was a retrospective pre-test post-test quasi-experimental design. Weekly in situ simulation events were facilitated by an interdisciplinary team in a high-volume ED in Hamilton, Ontario that sees an average of 185 patients per day. To date, 34 simulation events were held between January 18, 2019 and November 22, 2019, and included neonatal, paediatric and obstetric emergencies, and adult codes. There was an average of 20 patients presenting to the ED during these events. Events included a debrief, and typically lasted 60 minutes in total. Participants included individuals from various disciplines working on shift at the time of the event. Questionnaires were administered via email following the event, in which participants were asked to rank their comfort with emergency codes before and after the simulation using two 5-point Likert scales. The data from 39 questionnaires was analyzed. T-tests were used to analyze differences in self-reported comfort scores. Results: Questionnaire responders included nurses (41%), respiratory therapists (26%), resident physicians (10%), paramedics (3%), attending physicians (3%), students of various disciplines (10%) and other (7%). 38% of participants reported increases in comfort following simulation when compared to prior. Using the 5-point scale, the average reported score for comfort pre-simulation was 3.59 (95% CI 3.30–3.88), and the average post-simulation score was 3.97 (95% CI 3.76–4.19, p = 0.03). Conclusion: Our results demonstrate that weekly interprofessional in situ simulation is feasible in a high-volume ED, and significantly improves self-reported provider comfort with the identification and management of high-acuity, low-frequency events. This warrants the implementation of this simulation design to improve staff confidence and has implications for its potential role in improving team dynamics and patient safety.